2017
DOI: 10.1186/s40104-017-0152-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the immune effects of Scutellaria baicalensis on blood leukocytes and selected organs of the chicken’s lymphatic system

Abstract: BackgroundThe health of chickens and the welfare of poultry industry are central to the efforts of addressing global food security. Therefore, it is essential to study chicken immunology to maintain and improve its health and to find novel and sustainable solutions. This paper presents a study on investigation of the effect of Scutellaria baicalensis root (SBR) on the immune response of broiler chicken, especially on lymphocytes and heterophils reactivity, regarding their contribution to the development of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
(40 reference statements)
1
17
1
Order By: Relevance
“…In this study, we first determined the effect of dietary baicalein supplementation on growth performance and organ weights of broilers during the first week post-hatch. The decrease in body weight and average daily weight gain in response to the middle and high levels of baicalein supplementation was consistent with the observation that 0.5% supplementation of S. baicalensis root, which contains 19.3 ± 2.3 mg of baicalein and 214.5 ± 13.3 mg total flavonoids per gram of dry matter, reduced the body weight of 42-day old Hubbard Hi-Y chickens (Króliczewska et al, 2017). In contrast, supplementation of 1.0 and 1.5% of S. baicalensis root increased body weight and body weight gain of these birds (Króliczewska et al, 2017), which was similar to what was observed in 42-day old Arbor Acres chickens that were fed diets containing 100 and 200 mg/kg baicalein (Zhou et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, we first determined the effect of dietary baicalein supplementation on growth performance and organ weights of broilers during the first week post-hatch. The decrease in body weight and average daily weight gain in response to the middle and high levels of baicalein supplementation was consistent with the observation that 0.5% supplementation of S. baicalensis root, which contains 19.3 ± 2.3 mg of baicalein and 214.5 ± 13.3 mg total flavonoids per gram of dry matter, reduced the body weight of 42-day old Hubbard Hi-Y chickens (Króliczewska et al, 2017). In contrast, supplementation of 1.0 and 1.5% of S. baicalensis root increased body weight and body weight gain of these birds (Króliczewska et al, 2017), which was similar to what was observed in 42-day old Arbor Acres chickens that were fed diets containing 100 and 200 mg/kg baicalein (Zhou et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, baicalein supplementation was associated with decreased average daily food intake, whereas it was increased in 42-day Hi-Y chickens (Króliczewska et al, 2017) and unchanged in 42-day Arbor Acres broilers (Zhou et al, 2019). Weekly food intake was not affected over the course of 8 weeks of feeding a baicalein-supplemented high-fat diet (500 mg/kg) to middle-aged mice (Fu et al, 2014).…”
Section: Discussioncontrasting
confidence: 49%
“…Ishfaq et al [ 111 ] also showed that baicalin treatment could effectively prevent Mycoplasma gallinarum -induced inflammation, apoptosis, and energy metabolism dysfunction, providing a basis for new therapeutic targets to control M. gallinarum infection. However, Króliczewska et al [ 112 ] found that excessive supplementation of S. baicalensis roots (5–15 g/kg diet) may cause immunosuppression and may have a negative impact on the development of immune organs. S. baicalensis roots inhibited the formation of radially segmented nuclei, showing anti-metastatic properties and phagocytosis of chicken heterophils.…”
Section: Application Of S Baicalensis In Sustainable Animal Production For Better Performancementioning
confidence: 99%
“…It is clear that herbal medicine is the most ancientest approach worldwide application to treat diseases (Disch et al, 2017). The S. radix is extensively applied as a medicinal plant for remedy of diverse diseases and food supplement (Ohtsutki et al, 2009, Zhou et al, 2016, and Króliczewska et al, 2017. S. radix contains high concentrations of flavones and flavone glycosides (baicalein (Yue et al, 2012), wogonin (Huang et al, 2003) and their glycosides), which are also the main active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…S. radix contains high concentrations of flavones and flavone glycosides (baicalein (Yue et al, 2012), wogonin (Huang et al, 2003) and their glycosides), which are also the main active compounds. Flavones and flavone glycosides in S. radix are used effectively for improving immunity (Króliczewska et al, 2017, andCho et al, 2013), antiinflammatory (Yoon et al, 2009), antiviral (Zhong et alI., 2013), anticancer (Sato et al, 2013), antibacterial (Kim and Nam, 2017) and other biological activities (Jung et al, 2012).…”
Section: Introductionmentioning
confidence: 99%